Send for me [large type] - Fox, Lauren (Thorndike press large print romance, 2021)
An achingly beautiful work of historical fiction that moves between Germany on the eve of World War II and present-day Wisconsin, unspooling a thread of love, longing, and the powerful bonds of family. Annelise is a dreamer: imagining her future while working at her parents' popular bakery in Feldenheim, Germany, anticipating all the delicious possibilities yet to come. There are rumors that anti-Jewish sentiment is on the rise, but Annelise and her parents can't quite believe that it will affect them; they're hardly religious at all. As Annelise falls in love, marries, and gives birth to her daughter, the dangers grow closer: a brick thrown through her window; a childhood friend who cuts ties with her; customers refusing to patronize the bakery. Luckily Annelise and her husband are given the chance to leave for America, but they must go without her parents, whose future and safety are uncertain. Two generations later, in a small midwestern city, Annelise's granddaughter, Clare, is a young woman newly in love. When she stumbles upon a trove of her great-grandmother's letters from Germany, she sees the history of her family's sacrifices in a new light, and suddenly she's faced with an impossible decision: to choose the past, or her future without them. A novel of dazzling emotional richness, Send for Me is a major departure for this acclaimed author, an epic and intimate exploration of mothers and daughters, duty and obligation, hope and forgiveness. --